Our experience with pectoralis major flap for management of sternal dehiscence: A review of 25 cases - Parag Sahasrabudhe; Ranjeet Jagtap; Pankaj Waykole; Nikhil Panse; Pallavi Bhargava; Sampada Patwardhan (Indian Journal of Plastic Surgery)
Objective: To report our experience of the pectoralis major flap as the treatment modality for post coronary artery bypass sternal wound dehiscence. Materials and Methods: A retrospective study of 25 open heart surgery cases, performed between January 2006 and December 2010 at Deenanath Mangeshkar Hospital, Pune, was carried out. Unilateral or bilateral pectoralis major muscle flap by the double breasting technique using rectus extension was used in the management of these patients. The outcome was assessed on the basis of efficacy of flap surgery in achieving wound healing and post-surgery shoulder joint movements to evaluate donor site morbidity. The follow-up ranged from 5 months to 3.5 years. Results: Twenty-three (92%) patients were discharged with complete wound closure. One patient (4%) had wound dehiscence after flap surgery. One patient (4%) died in the hospital in the immediate postoperative period due to mediastinitis. No recurrent sternum infection has occurred till date in 24 patients (96%). For one patient (4%) who had wound dehiscence, daily dressing was done and wound healing was achieved with secondary intension. At follow-up, shoulder joint movements were normal in all the patients. Conclusions: The double breasting technique of the pectoralis major muscle flaps with rectus sheath extension is efficient in covering the entire length of the defect and can reduce the morbidity, without affecting the function of the shoulder joint.